High thermal conductivity aluminum nitride composite material and preparation method thereof
Patent Information
- Application Number
- CN202411374461.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2044-09-29
AI Technical Summary
[0004]为了改善目前AlN陶瓷导热性能不佳的问题,本申请提供一种高导热氮化铝复合材料及其制备方法
[0031]1、由于本申请氧化钇在浆料中的添加量,优选氧化钇的添加量为6%,使得氧化钇在浆料中能够保持颗粒状,不易黏连,进而能够维持氮化铝陶瓷晶粒之间的面接触,为声子传播提供顺畅的通道,从而进一步提高复合材料的导热效果。而一些常规的氮化铝陶瓷,添加了氧化钇之后,氧化钇颗粒较易黏连,从而减少氮化铝晶粒之间的面接触以及通道,使得陶瓷复合材料的导热率降低。此外,通过优化氧化钇的添加量,能够降低陶瓷的烧结温度。
Smart Images

Figure BDA0005068349650000111 
Figure BDA0005068349650000121
Abstract
Description
Technical Field
[0001] This application relates to the technical field of ceramics, and more specifically, to a high thermal conductivity aluminum nitride composite material and its preparation method. Background Technology
[0002] Commonly used ceramic heat dissipation materials mainly include Al2O3, BeO, SiC, and AlN. Among these ceramic materials, Al2O3 is currently the most widely used and mature heat dissipation material, but its low thermal conductivity prevents it from meeting high thermal conductivity requirements. BeO has good overall performance, but its toxicity limits its application. Although SiC has high thermal conductivity, its preparation process is complex, costly, and has a high dielectric constant.
[0003] In comparison, AlN ceramics possess excellent thermal conductivity and are non-toxic with thermal conductivity similar to that of silicon, making them ideal thermal conductive materials and attracting widespread attention from academia and industry. With the development of science and technology and industry, the demand for high thermal conductivity irregularly shaped ceramic components is increasing rapidly. However, the thermal conductivity of current AlN ceramics still has some shortcomings. Summary of the Invention
[0004] To address the current issue of poor thermal conductivity in AlN ceramics, this application provides a high thermal conductivity aluminum nitride composite material and its preparation method.
[0005] This application provides a high thermal conductivity aluminum nitride composite material, which adopts the following technical solution:
[0006] In a first aspect, this application provides a high thermal conductivity aluminum nitride composite material, comprising the following components by weight: 950-960 parts aluminum nitride; 55-65 parts yttrium oxide; 85-95 parts PVB; 50-60 parts DBP; 15-18 parts castor oil; 0-10 parts recycled material; and 380-400 parts solvent.
[0007] By adopting the above technical solution, aluminum nitride is a ceramic material with high thermal conductivity, excellent electrical insulation properties, low coefficient of expansion, corrosion resistance, and wear resistance, making it an excellent semiconductor material. Aluminum nitride relies on phonons for heat transfer. The surface contact between aluminum nitride ceramic grains provides a smooth channel for phonon propagation. The second phase and various defects in the crystal lattice dissipate heat from phonons, thus reducing thermal conductivity. Since oxygen can undergo solid solution with aluminum nitride to form oxygen defects, these defects scatter phonons, further reducing thermal conductivity. Therefore, this application uses yttrium oxide as a sintering aid in the slurry. The addition of yttrium oxide effectively reduces the oxygen content in aluminum nitride, further inducing a carbothermic reduction reaction, thereby effectively improving the thermal conductivity of the ceramic material.
[0008] Optional components include the following by weight: 950-960 parts aluminum nitride; 60 parts yttrium oxide; 85-95 parts PVB; 50-60 parts DBP; 15-18 parts castor oil; 0-10 parts recycled material; and 380-400 parts solvent.
[0009] By adopting the above technical solution, the amount of yttrium oxide added to the slurry was optimized, with a preferred addition amount of 6%. This ensures that the yttrium oxide remains in a particulate state in the slurry, preventing it from easily agglomerating. This maintains the surface contact between aluminum nitride ceramic grains, providing a smooth channel for phonon propagation and further improving the thermal conductivity of the composite material. In contrast, in some conventional aluminum nitride ceramics, the addition of yttrium oxide makes the yttrium oxide particles more prone to agglomeration, reducing the surface contact and channels between aluminum nitride grains and thus lowering the thermal conductivity of the ceramic composite. Furthermore, optimizing the amount of yttrium oxide can lower the sintering temperature of the ceramic.
[0010] Optionally, it may also include 10-20 parts by weight of boron-containing resin.
[0011] By adopting the above technical solution, boron-containing resin is added to the slurry. The addition of boron can effectively promote the graphitization of the resin, and boron can react with the active functional groups of the resin, transforming the small molecule volatile components generated during resin pyrolysis into stable components retained in the matrix, thereby improving the density and structural stability of the slurry. The introduction of resin materials can encapsulate and bind the various components in the slurry, and the carbon generated by the resin during sintering can undergo a carbothermic reduction reaction with the oxide layer on the surface of aluminum nitride particles, effectively reducing or eliminating the oxide layer on the surface of aluminum nitride, which is beneficial to phonon transfer between aluminum nitride particles, thereby stabilizing and improving the thermal conductivity of the composite material.
[0012] Optionally, the boron-containing resin includes boron carbide-modified phenolic resin, wherein the mass ratio of boron carbide to phenolic resin is 6-7:3-4.
[0013] By employing the above technical solution, phenolic resin is added to the slurry. During sintering, the carbon-carbon bonds of the phenolic resin break, generating phenol and cresol. Then, the methylene groups react with the hydroxyl groups, leading to hydrocarbon transfer, or the hydroxyl functional groups react with each other to form ether bonds. As the temperature increases, further deoxygenation and dehydrogenation reactions occur, gradually transforming the resin into carbon materials. These carbon materials can undergo carbothermic reduction reactions with the oxide layer on the surface of aluminum nitride, reducing or eliminating the oxide layer and thus promoting mass transfer in aluminum nitride, improving the density and thermal conductivity of the ceramic. Modifying phenolic resin with boron carbide enables the carbonization and graphitization of the phenolic resin at lower temperatures. During heat treatment, boron carbide reacts with the active functional groups of the phenolic resin, transforming the small-molecule volatile components generated from the cracking of the phenolic resin into stable components, thereby improving the density and structural stability of the ceramic.
[0014] Optionally, the boron-containing resin may further include a boron-containing epoxy resin, wherein the boron-containing epoxy resin comprises a boron-containing filler and an epoxy resin.
[0015] By adopting the above technical solution, the thermal conductivity of epoxy resin can be effectively improved by using boron-containing filler in combination with epoxy resin. In addition, in-situ cracked carbon can be generated during the cracking process of epoxy resin. The cracked carbon can also react with the oxide layer on the surface of aluminum nitride, maintaining the mass transfer effect between aluminum nitride grains. Together with boron-containing phenolic resin, it can improve the density and thermal conductivity of ceramic materials.
[0016] Optionally, the preparation method of the boron-containing filler includes the following steps: stirring and mixing sodium chloride, PH-DDM and boron nitride, pressing into tablets, heating and curing, water bath impregnation, drying, and crushing to obtain the boron-containing filler.
[0017] By employing the above technical solution and using a sacrificial salt template method, a three-dimensional interconnected network with a honeycomb structure is obtained. Furthermore, PH-DDM is carbonized and loaded onto the boron nitride surface through heat curing, thereby forming a three-dimensional interlaced thermally conductive network structure. Modifying the epoxy resin with boron-containing fillers possessing a thermally conductive network structure increases the aluminum nitride mass transfer channels, effectively improving the thermal conductivity of the ceramic.
[0018] Optionally, the boron nitride is boron nitride modified with tannic acid.
[0019] By adopting the above technical solution, boron nitride is modified with tannic acid. Tannic acid has a large number of catechol or triol groups, which can participate in non-covalent interactions, such as ion pairing and hydrogen bonding. Therefore, after modifying boron nitride, the dispersion uniformity of boron nitride in epoxy resin can be improved, that is, boron-containing raw materials can be uniformly dispersed in the slurry, so that the ceramic can obtain a uniform thermal conductivity.
[0020] Optionally, it may also include 3-5 parts of silicon carbide.
[0021] By adopting the above technical solution, silicon carbide fibers have excellent properties such as high strength, high thermal conductivity, superplasticity and superelasticity. When added to ceramics, they can effectively improve the density and strength of ceramics by using the fibers to pull the various components in the ceramics.
[0022] Secondly, this application provides a method for preparing a high thermal conductivity aluminum nitride composite material, which adopts the following technical solution:
[0023] A method for preparing a high thermal conductivity aluminum nitride composite material includes the following steps: S1, raw material weighing: aluminum nitride, yttrium oxide, PVB, DBP, castor oil, recycled material and solvent are weighed according to the weight parts, mixed, and ball-milled to obtain a slurry;
[0024] S2. Degassing treatment: Degassing the slurry using a vacuum pump;
[0025] S3. Casting and molding: The degassed slurry is placed on a casting machine for casting, molding, drying, and cutting to obtain the molded product.
[0026] S4. Printing and molding: Print tungsten paste heating circuits on the molded product, roll the rod, and form it to obtain a semi-finished product;
[0027] S5. Sintering and Shipping: The semi-finished product is placed in a container for sintering treatment, and then inspected and shipped.
[0028] Optionally, the aluminum nitride is refined aluminum nitride that has been ball-milled for 25-30 hours.
[0029] By adopting the above technical solution, ball milling of aluminum nitride can refine the grains of aluminum nitride, introduce lattice distortion, and introduce an appropriate amount of Fe element, thereby effectively reducing the sintering temperature of aluminum nitride, which is beneficial to the production of ceramics.
[0030] In summary, this application has the following beneficial effects:
[0031] 1. The preferred amount of yttrium oxide added to the slurry in this application is 6%. This ensures that the yttrium oxide remains particulate in the slurry, preventing it from easily agglomerating. This maintains the surface contact between aluminum nitride ceramic grains, providing a smooth channel for phonon propagation and further improving the thermal conductivity of the composite material. In contrast, in some conventional aluminum nitride ceramics, the added yttrium oxide particles tend to agglomerate, reducing the surface contact and channels between aluminum nitride grains, thus lowering the thermal conductivity of the ceramic composite. Furthermore, optimizing the amount of yttrium oxide added can lower the sintering temperature of the ceramic.
[0032] 2. In this application, phenolic resin is preferably added to the slurry. During sintering, the carbon-carbon bonds of the phenolic resin break, generating phenol and cresol. Then, the methylene groups react with the hydroxyl groups, leading to hydrocarbon transfer, or the hydroxyl functional groups react with each other to form ether bonds. As the temperature increases, further deoxygenation and dehydrogenation reactions occur, gradually transforming into carbon materials. The carbon materials can undergo a carbothermic reduction reaction with the oxide layer on the surface of aluminum nitride, reducing or eliminating the oxide layer on the surface of aluminum nitride, thereby promoting the mass transfer of aluminum nitride and improving the density and thermal conductivity of the ceramic. Modifying phenolic resin with boron carbide can achieve the carbonization and graphitization of phenolic resin at a lower temperature. During heat treatment, boron carbide can react with the active functional groups of phenolic resin, transforming the small molecule volatile components generated by the cracking of phenolic resin into stable components, thereby improving the density and structural stability of the ceramic.
[0033] 3. This application employs a sacrificial salt template method to obtain a three-dimensional interconnected network with a honeycomb structure. Furthermore, PH-DDM is carbonized and loaded onto the boron nitride surface via heat curing, thereby forming a three-dimensional interlaced thermally conductive network structure. Modifying the epoxy resin with boron-containing fillers possessing a thermally conductive network structure increases the aluminum nitride mass transfer channels, effectively improving the thermal conductivity of the ceramic.
[0034] 4. The method of this application ball mills aluminum nitride, which can refine the aluminum nitride grains, introduce lattice distortion and introduce an appropriate amount of Fe element, thereby effectively reducing the sintering temperature of aluminum nitride, which is beneficial to the production of ceramics. Detailed Implementation
[0035] The present application will be further described in detail below with reference to the embodiments.
[0036] The instruments and equipment used in this embodiment are shown below, but are not limited thereto:
[0037] Pharmaceuticals: The phenolic resin is phenolic resin No. 213 from Tianjin Daying Resin Co., Ltd. The viscosity of the phenolic resin at 20℃ is 0.8-1.53 Pa·s, the solid content is 80±3%, and the power content is not higher than 21%; the boron carbide has a particle size of 2.5-3.5μm and a purity of 85%; the recycled material is aluminum nitride scraps that can be collected and reused.
[0038] Preparation Example
[0039] Preparation Example 1
[0040] Phenolic resin and boron carbide were mixed at a mass ratio of 7:3 and stirred at a speed of 100 r / min to prepare boron-containing phenolic resin.
[0041] Preparation Example 2
[0042] Take 0.027g of tannic acid and 3g of boron nitride and disperse them in 100mL of deionized water. Disperse by ultrasonication for 30min, stir magnetically for 8h, filter, wash, and dry at 40℃ to obtain tannic acid modified boron nitride.
[0043] Preparation Example 3
[0044] 0.027 g of tannic acid and 3 g of boron nitride were dispersed in 100 mL of deionized water and ultrasonically dispersed for 30 min. The mixture was then magnetically stirred for 8 h. 0.56 g of copper sulfate was weighed and dissolved in 100 mL of deionized water to obtain a copper solution. The copper solution was mixed with the boron nitride solution to obtain a mixed solution. The pH of the mixed solution was adjusted to 7.4 using NaOH solution, and the temperature of the mixed solution was adjusted to 50 °C and stirred for 4 h. The mixture was filtered and separated, washed three times with water and alcohol, and dried at 40 °C for 24 h to obtain complex-modified boron nitride.
[0045] Preparation Example 4
[0046] A solution of 1.98 g of 4,4-diaminodiphenylmethane, 1.32 g of paraformaldehyde, and 1.88 g of phenol was added to 30.0 mL of toluene solution, and the mixture was heated at 80 °C for 5 hours. The mixture was then cooled to room temperature and washed three times with 30 mL of 0.1 mol / L sodium hydroxide aqueous solution and 30 mL of deionized water until the pH was constant at 7.0 ± 1.0. The solvent was then removed by rotary evaporation, followed by vacuum drying at 50 °C for 24 hours to obtain a light yellow granular solid (yield 83%), named PH-DDM.
[0047] 2g NaCl, 0.15g PH-DDM, and 0.30g boron nitride were mixed and stirred. The mixed powder was placed in a tablet press for tableting and cured at 180℃ for 2 hours to obtain a cured product. The cured product was repeatedly washed in a 60℃ water bath, dried at 80℃, crushed, and then repeatedly washed in a 60℃ water bath and dried at 80℃ again to obtain a boron-containing filler. Epoxy resin and boron-containing filler were mixed at a mass ratio of 7:3 to obtain a boron-containing epoxy resin.
[0048] Preparation Example 5
[0049] 2g NaCl, 0.15g PH-DDM, and 0.30g boron nitride prepared in Preparation Example 2 were mixed and stirred. The mixed powder was placed in a tablet press for tableting and cured at 180℃ for 2 hours to obtain a cured product. The cured product was repeatedly washed in a 60℃ water bath, dried at 80℃, crushed, and then repeatedly washed in a 60℃ water bath and dried at 80℃ again to obtain a boron-containing filler. Epoxy resin and boron-containing filler were mixed at a mass ratio of 7:3 to obtain a boron-containing epoxy resin.
[0050] Preparation Example 6
[0051] 2g NaCl, 0.15g PH-DDM, and 0.30g boron nitride prepared in Preparation Example 3 were mixed and stirred. The mixed powder was placed in a tablet press for tableting and cured at 180℃ for 2 hours to obtain a cured product. The cured product was repeatedly washed in a 60℃ water bath, dried at 80℃, crushed, and then repeatedly washed in a 60℃ water bath and dried at 80℃ again to obtain a boron-containing filler. Epoxy resin and boron-containing filler were mixed at a mass ratio of 7:3 to obtain a boron-containing epoxy resin.
[0052] Preparation Example 7
[0053] Boron-containing phenolic resin and garnet powder were mixed at a mass ratio of 7:3 and magnetically stirred for 30 minutes to obtain boron-containing phenolic resin.
[0054] Preparation Example 8
[0055] Weigh out 10% SiC nanofibers and place them in a tube furnace. Introduce CH4 and N2, and then perform CVD on the SiC nanofibers. nf PyC coating was deposited on the surface. Reaction conditions were controlled as follows: temperature 1100℃, CH4 to N2 flow rate ratio 1:2, total system pressure 20 kPa, and deposition time 60 min. SiC nanofibers coated with pyrolyzed carbon were prepared under a CH4 gas flow rate of 20 mL / min.
[0056] Example
[0057] Examples 1-3
[0058] On the one hand, this application provides a high thermal conductivity aluminum nitride composite material, comprising aluminum nitride, yttrium oxide, PVB, DBP, castor oil, recycled materials and solvent, the specific quantities of which are shown in Table 1.
[0059] The solvents are equal masses of ethanol and butanone.
[0060] On the other hand, this application provides a method for preparing a high-pressure solid phosphate-type cathode material, comprising the following steps:
[0061] S1. Raw material weighing: Weigh aluminum nitride, yttrium oxide, PVB, DBP, castor oil, recycled materials and solvent according to the weight parts, mix them, and ball mill them at 30 r / s for 24 h to obtain a slurry;
[0062] S2. Degassing treatment: The slurry is degassed for 30 minutes using a vacuum pump at 0.07 MPa.
[0063] S3. Casting and molding: The degassed slurry is placed on a casting machine at a speed of 10m / min and a casting blade height of 1.0mm for casting and molding. It is then dried at 120℃ and cut to obtain the molded product.
[0064] S4. Printing and molding: Print tungsten paste heating circuits on the molded product, roll the rod, and form it to obtain a semi-finished product;
[0065] S5. Sintering and shipping: Place the semi-finished product in a container and sinter at 1830℃ for 36 hours, then inspect and ship.
[0066] Table 1. Slurry composition of Examples 1-3
[0067] Aluminum nitride 950 955 960 Yttrium oxide 55 60 65 PVB 85 90 95 DBP 50 55 60 castor oil 15 16.8 18 Recycled materials 0 0 0 solvent 380 390 400
[0068] Example 4
[0069] The difference from Example 2 is that: an equal mass of refined aluminum nitride that has been ball-milled for 30 hours is used instead of the aluminum nitride in Example 2 to prepare the aluminum nitride composite material.
[0070] Example 5
[0071] The difference from Example 2 is that the slurry also includes 15 kg of the boron-containing phenolic resin prepared in Example 1, to prepare the aluminum nitride composite material.
[0072] Example 6
[0073] The difference from Example 2 is that the slurry also includes 10 kg of boron-containing phenolic resin prepared in Example 1 and 5 kg of boron-containing epoxy resin prepared in Example 4, to prepare aluminum nitride composite material.
[0074] Example 7
[0075] The difference from Example 2 is that the slurry also includes 10 kg of boron-containing phenolic resin prepared in Example 1 and 5 kg of boron-containing epoxy resin prepared in Example 5, to prepare aluminum nitride composite material.
[0076] Example 8
[0077] The difference from Example 2 is that the slurry also includes 10 kg of boron-containing phenolic resin prepared in Example 1 and 5 kg of boron-containing epoxy resin prepared in Example 6, to prepare aluminum nitride composite material.
[0078] Example 9
[0079] The difference from Example 2 is that the slurry also includes 10 kg of boron-containing phenolic resin prepared in Example 1 and 5 kg of boron-containing phenolic resin prepared in Example 7, to prepare aluminum nitride composite material.
[0080] Example 10
[0081] The difference from Example 2 is that the slurry also includes 4 kg of silicon carbide fiber to prepare aluminum nitride composite material.
[0082] Example 11
[0083] The difference from Example 2 is that the slurry also includes 4 kg of silicon carbide fiber prepared in Example 8 to prepare aluminum nitride composite material.
[0084] Comparative Example
[0085] Comparative Example 1
[0086] The difference between this comparative example and Example 2 is that yttrium oxide was not added in this comparative example to prepare aluminum nitride composite material.
[0087] Comparative Example 2
[0088] The difference between this comparative example and Example 2 is that the amount of yttrium oxide added in this comparative example is 30 kg, and aluminum nitride composite material is prepared.
[0089] Performance testing
[0090] (1) Thermal conductivity test: Thermal conductivity was measured using the transient flat plate heat source method (TPS2500S, HotDisk). Test parameters: probe output power was 20.60mW, test temperature was room temperature, and the machine was preheated for two hours before the test. Two samples of equal size and smooth surface were prepared before the test.
[0091] Three samples were prepared on tinplate according to GB1727-79 General Preparation Method of Coating Film. After the coating film was completely dry, the test was carried out under constant temperature and humidity conditions.
[0092] (2) Density test: The density of sintered ceramic bodies was measured using the Archiamde water displacement method.
[0093] Table 2 Performance Testing
[0094]
[0095]
[0096] By comparing the performance test results in Table 2, we can find that:
[0097] 1. A comparison of Examples 1-3, Example 4, and Comparative Examples 1-2 reveals that the thermal conductivity and density of the ceramics prepared in Examples 1-4 are improved. This indicates that the amount of yttrium oxide added to the slurry was optimized in this application, preferably at 6%. This allows the yttrium oxide to remain granular in the slurry, preventing it from easily agglomerating. This, in turn, maintains the surface contact between the aluminum nitride ceramic grains, providing a smooth channel for phonon propagation and further improving the thermal conductivity of the composite material. Ball milling of aluminum nitride refines its grains, introduces lattice distortion, and introduces an appropriate amount of Fe, effectively reducing the sintering temperature of aluminum nitride and benefiting ceramic production.
[0098] 2. A comparison between Examples 5-6 and Example 2 reveals that the thermal conductivity and density of the ceramics prepared in Examples 5-6 are improved. This indicates that the addition of boron-containing resin to the slurry in this application effectively promotes resin graphitization. Furthermore, boron can react with the active functional groups of the resin, transforming the small-molecule volatile components generated during resin pyrolysis into stable components retained in the matrix, thereby improving the density and structural stability of the slurry. The introduction of resin materials can encapsulate and bind the various components in the slurry. Additionally, the carbon generated during resin sintering can undergo a carbothermic reduction reaction with the oxide layer on the surface of aluminum nitride particles, effectively reducing or eliminating the oxide layer on the aluminum nitride surface. This facilitates phonon transfer between aluminum nitride particles, thereby stabilizing and improving the thermal conductivity of the composite material.
[0099] 3. A comparison between Examples 7-8 and Example 2 reveals that the thermal conductivity and density of the ceramics prepared in Examples 7-8 are improved. This indicates that the modification of boron nitride with tannic acid in this application has a large number of catechol or vicinal triol groups, which can participate in non-covalent interactions, such as ion pairing and hydrogen bonding. Therefore, after modifying boron nitride, the dispersion uniformity of boron nitride in epoxy resin can be improved, that is, the boron-containing raw materials can be uniformly dispersed in the slurry, so that the ceramics can obtain a uniform thermal conductivity effect.
[0100] 4. A comparison between Example 9 and Example 2 reveals that the thermal conductivity and density of the ceramic prepared in Example 9 are both improved. This indicates that modifying phenolic resin with garnet micropowder in this application can improve the strength of phenolic resin, thereby improving the strength of the ceramic.
[0101] 5. A comparison between Examples 11-12 and Example 2 reveals that the thermal conductivity and density of the ceramics prepared in Examples 10-11 are improved. This indicates that silicon carbide fibers in this application possess excellent properties such as high strength, high thermal conductivity, superplasticity, and superelasticity. When added to ceramics, the fibers can effectively improve the density and strength of the ceramics by drawing the various components together. Furthermore, carbon-coating silicon carbide fibers can further improve their strength and toughness, thereby further improving the density and strength of the ceramics.
[0102] This specific embodiment is merely an explanation of this application and is not intended to limit it. After reading this specification, those skilled in the art can make modifications to this embodiment without contributing any inventive step, but such modifications are protected by patent law as long as they fall within the scope of the claims of this application.
Claims
1. A high thermal conductivity aluminum nitride composite material, characterized in that, Includes the following substances in parts by weight: 950-960 parts of aluminum nitride; 55-65 parts of yttrium oxide; 85-95 PVB servings; 50-60 DBPs; 15-18 parts castor oil; 0-10 parts of recycled material; Solvent: 380-400 parts; It also includes 10-20 parts by weight of boron-containing resin; The boron-containing resin includes boron carbide-modified phenolic resin, and the mass ratio of boron carbide to phenolic resin is 6-7:3-4. The boron-containing resin further includes a boron-containing epoxy resin, which comprises a boron-containing filler and an epoxy resin. The preparation method of the boron-containing filler includes the following steps: stirring and mixing sodium chloride, PH-DDM and boron nitride, pressing into tablets, heating and curing, water bath impregnation, drying, crushing, and obtaining the boron-containing filler; The boron nitride is boron nitride modified with tannic acid.
2. The high thermal conductivity aluminum nitride composite material according to claim 1, characterized in that: Includes the following substances in parts by weight: 950-960 parts of aluminum nitride; 60 parts of yttrium oxide; 85-95 PVB servings; 50-60 DBPs; 15-18 parts castor oil; 0-10 parts of recycled material; Solvent 380-400 parts.
3. The high thermal conductivity aluminum nitride composite material according to claim 1, characterized in that: It also includes 3-5 parts of silicon carbide.
4. A method for preparing a high thermal conductivity aluminum nitride composite material according to any one of claims 1-3, characterized in that, Includes the following steps: S1. Raw material weighing: Weigh the above raw materials according to the weight parts, mix them, and ball mill them to obtain a slurry; S2. Degassing treatment: Degassing the slurry using a vacuum pump; S3. Casting and molding: The degassed slurry is placed on a casting machine for casting, molding, drying, and cutting to obtain the molded product. S4. Printing and molding: Print tungsten paste heating circuits on the molded product, roll the rod, and form it to obtain a semi-finished product; S5. Sintering and Shipping: The semi-finished product is placed in a container for sintering treatment, and then inspected and shipped.
5. The method for preparing a high thermal conductivity aluminum nitride composite material according to claim 4, characterized in that: The aluminum nitride is refined aluminum nitride that has been ball-milled for 25-30 hours.
Citation Information
Patent Citations
Aluminum nitride ceramic composite material and preparation method thereof
CN104402480A
Preparation method of aluminum nitride ceramic substrate with high thermal conductivity for high power microelectronic devices
CN106431419A